(untitled) (Research, Society and Development, 2025)
Biochemical, physiological and immunological reactions resulting from human homeostasis can be better explained with an accurate printed model of reality. Creating biological structures through 3D printing helps healthcare students better understand complex subjects. Going beyond the slide bias and animated videos, to physical tactile and assembly structures, so that the student becomes the protagonist, helps to stimulate students’ knowledge and educational knowledge. This study seeks to present a proposed application for the 3D printer in the educational context, at a university in the city of Gurupi-TO (UNIRG), associating it with problem solving. On that occasion, students used knowledge acquired in the classroom to address the problem that permeates several educational institutions: the lack of teaching material for use in practical activities. From there, use the active Design Thinking methodology to assist in the process, building ideas and prototypes for use as teaching material. The results indicate that the 3D printer can facilitate the teaching of content that makes up the academic curriculum, whether by encouraging students to build models or using ready-made models as teaching material.